16S rRNA Gene-targeted TTGE in Determining Diversity of Gut Microbiota during Acute Diarrhoea and Convalescence - Monira, Shirajum; Shabnam, Syeda Antara; Alam, Nur Haque; Endtz, Hubert Ph.; Cravioto, Alejandro; Alam, Munirul (Journal of Health, Population and Nutrition, 2012)
The human gut microbiota play a vital role in health and nutrition but are greatly modified during severe diarrhoea due to purging and pathogenic colonization. To understand the extent of loss during and after diarrhoea, faecal samples collected from children (n=21) suffering from acute diarrhoea and from their healthy siblings (n=9) were analyzed by 16S rRNA gene-targeted universal primer polymerase chain reaction (PCR), followed by temporal temperature gradient gel electrophoresis (TTGE). The gut microbiota decreased significantly as indicated by the number of TTGE bands at day 0 of acute diarrhoea [patients vs healthy siblings: 11±0.9 vs 21.8±1.1 (mean±standard error), p<0.01]. The number of bands showed a steady increase from day 1 to day 7; however, it remained significantly less than that in healthy siblings (15±0.9, p<0.01). These results suggest that appropriate therapeutic and post-diarrhoeal nutritional intervention might be beneficial for the early microbial restoration and recovery. DOI: http://dx.doi.org/10.3329/jhpn.v30i3.12287 J HEALTH POPUL NUTR 2012 Sep;30(3):250-256